Promising bacteria strains of the genus Bacillus in plant protection against fusariosis and mycotoxin contamination - V. V. Allakhverdyan; T. M. Sidorova; A. M. Asaturova (Юг России: экология, развитие)
Aim – to study the biocontrol properties of B. velezensis BZR 336g and B. velezensis BZR 517 strains against Fusarium pathogens using the fungus Fusarium graminearum as an example and to reduce the accumulation of deoxynivalenol (DON) and zearalenone (ZEN) in vitro.Materials and Methods. A study of the toxinogenicity of F. graminearum fungal strains was undertaken on rice and wheat grains and the effect of B. velezensis BZR 336g and B. velezensis BZR 517 strains on the growth of the fungus was studied on wheat grains and by the double cultures method. An experiment to study the effect of a liquid culture and supernatant of bacteria was carried out on wheat grains and the content of DON and ZEN in wheat grains was analyzed by HPLC and enzyme immunoassay.Results. It was found that two strains of the fungus F. graminearum were able to produce a high level of mycotoxins, while the strain F. graminearum 60318 had a higher growth rate. The B. velezensis BZR 336g and B. velezensis BZR 517 strains produced lipopeptide exometabolites and inhibited the growth of the F. graminearum 60318 strain. in vitro, while the content of ZEN remained at the control level.Conclusion. The ability of two strains of bacteria B. velezensis BZR 336g and B. velezensis BZR 517 to suppress the growth of the fungus F. graminearum 60318, as well as to inhibit the accumulation of mycotoxins in wheat grain in vitro, suggests that an increase in the content of antagonist bacteria B. velezensis BZR 336g and B. velezensis BZR 517 in the wheat microbiota can contribute to the suppression of the growth and harm of the fungus F. graminearum 60318.